(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
The pet. ether (Pat. Ether), chloroform, ethanol extracts and pure compound of alpha amyrin from fruits of Artocarpus gomezianus was examined for anthelmintic efficacy utilizing earthworm (Pheretima posthuma). Diverse amounts (25-100 mg/ml) of fruit extraction was evaluated within the bioassay. Albendazole (25 mg/ml) served as the reference criteria medicine, while purified water functioned as the regulate. The paralysis and mortality times of the worms were documented. Extracts shown considerable anthelmintic efficacy at higher concentration of 25 mg/ml. The extract of pet. ether, chloroform and ethanol had shown dose-dependent anthelmintic effect in comparison to the conventional medication albendazole. The pet. ether extract exhibited paralytic effects and time of death for Pheretima posthuma at doses of 25, 50, and 100 mg/ml exhibited a result of 48.33±0.62, 37.72±0.55, 27.87±1.50 and 60.46±0.43, 60.90±0.77 and 60.31±0.16 minutes respectively. The chloroform the extract demonstrated paralyzing effects and duration of death for Pheretima posthuma at the dosage concentrations of 25, 50, and 100 mg/ml were identified to be 62.22±1.93, 48.01±0.82 and 37.69±0.74 and 122.73±2.08, 81.05±0.87 and 60.85±0.87 minutes respectively. The ethanol extract exhibited paralytic effects and death time of P. posthuma with dose of 25, 50 and 100 mg/ml were found 56.08±1.24, 47.94±1.10, and 44.03±0.89 and 120.48±0.05, 90.42±0.02 and 80.27±0.85 minutes respectively. The observation with standard albendazole showed that time of paralysis and death was 60.40±0.02 and 120.40±0.02 minutes respectively. The a-amyrin showed immobilizing duration of Pheretima posthuma. The average paralyzing duration of P. posthuma with a dose of 25, 50 and 100 milligrams per milliliter were ascertained to be 35.18±0.12, 30.18±0.15 and 20.17±0.08 minutes respectively. In the meantime, Albendazole administered at a concentration of 25 mg/ml induced paralysis in the aforementioned helminthin 60.40±0.02 minutes. In the average duration Albendazole at a dosage of 25 mg/ml resulted in a mortality time for the aforementioned worm. 120.40±0.02 minutes. The a-amyrin showed more anthelmintic efficacy as compareto the conventional medication of albendazole.